Management Planning Water Resources in Balikpapan City, Indonesia: A Case Study - Mellyda Dharma Mulyawati; Agus Ferdinand; Jauchar B; Angga Kusuma Wijaya; Herdin Arie Saputra (Government & Resilience, 2024)
This study aims to investigate the role of water resource management in Balikpapan City, Indonesia, focusing on how the city government implements sustainable development and water governance practices. Using a qualitative approach and literature review, this research examines Balikpapan’s strategies for addressing water challenges amid climate change, population growth, and its role within the Indonesian Capital City (Ibu Kota Nusantara, IKN) area. Findings reveal that Balikpapan’s regional development plan has adopted a sustainable approach, emphasizing prevention and mitigation efforts to secure long-term water resources. In addition to constructing new infrastructure, Balikpapan is exploring collaboration with neighboring administrative areas to ensure a reliable water supply in the future. Nonetheless, there is a need for stronger partnerships with the private sector, especially to support technological innovations that, while potentially costly, could enhance water management. Public participation is also essential to prevent social conflicts and to ensure that development progresses fairly and inclusively. By engaging diverse stakeholders—including the government, private sector, and community—in planning and implementation, Balikpapan and IKN Nusantara can work towards sustainable development goals that prioritize environmental responsibility and meet the needs of all communities. This collaborative approach can foster sustainable, equitable solutions that align with global goals, supporting a resilient and water-secure future for Balikpapan and its surrounding areas.